Digital empowerment: how AyyKori is reshaping Bangladeshi local communities through local brand partnerships and digital marketing - Afrin, Sajia (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.